2018
DOI: 10.1093/mnras/sty322
|View full text |Cite
|
Sign up to set email alerts
|

Flux rope breaking and formation of a rotating blowout jet

Abstract: We analyzed a small flux rope eruption converted into a helical blowout jet in a fan-spine configuration using multi-wavelength observations taken by SDO, which occurred near the limb on 2016 January 9. In our study, first, we estimated the fanspine magnetic configuration with the potential field calculation and found a sinistral small filament inside it. The filament along with the flux rope erupted upward and interacted with the surrounding fan-spine magnetic configuration, where the flux rope breaks in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 75 publications
(119 reference statements)
1
31
0
Order By: Relevance
“…Additionally, we found that the jet rotates counterclockwise if viewed from the top to the footpoint N1 (see the attached movie of Fig. 4), indicating that there may be a flux rope that may be related to the filament before the reconnection (e.g., Joshi et al 2018). Furthermore, the rotation of the jet is also shown in the Hα Dopplergrams (Figs.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Additionally, we found that the jet rotates counterclockwise if viewed from the top to the footpoint N1 (see the attached movie of Fig. 4), indicating that there may be a flux rope that may be related to the filament before the reconnection (e.g., Joshi et al 2018). Furthermore, the rotation of the jet is also shown in the Hα Dopplergrams (Figs.…”
Section: Resultsmentioning
confidence: 65%
“…While magnetic reconnection is believed to occur in fan-spine configuration where there may be a mini-filament under the null point, and it can reconnect with spine lines and then form a jet (Joshi et al 2015;Li et al 2017;Xu et al 2017). Although magnetic reconnections associated with filaments, including small-scale filaments, are often reported during their eruptions (e.g., Joshi et al 2018;Yang et al 2017), the detailed process of magnetic reconnection is rarely noticed in the previous studies.…”
Section: Introductionmentioning
confidence: 97%
“…Taken together with the results of Panesar et al [66][67][68] they also claim that flux cancellation is the main process whereby the energy is stored prior to eruption in all jets and CMEs, and may also be involved in the triggering process. So far, the finding of blowout jets has been confirmed by many observational studies, and now we recognize that the vast majority of solar jets are caused by magnetic flux cancellation rather than flux emergence [63,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. Recently, high-resolution observational studies have shown that two-sided-loop jets are also associated with flux cancellations and include the eruption of mini-filaments inside the base arches [44,46,49,85,86], and two-sidedloop jets occurring in filament channels may be important for causing the eruption of large filaments [87].…”
Section: Observational Feature (A) Morphology and Classificationmentioning
confidence: 99%
“…Shen et al [63,69] studied two blowout jets and found that the erupting mini-filaments directly form the cool component of coronal jets (figure 2). Recently, more and more observational studies have confirmed that blowout jets are driven by mini-filament eruptions or filament channels [73][74][75][76][77][78][79][80][81][82][83][84]97,98]; some authors even proposed that all coronal jets originate from mini-filament eruptions, and their generation resembles the eruption of large-scale, energetic filament/CME eruptions [36,65,99].…”
Section: (B) Precursormentioning
confidence: 99%
“…Recent investigations have associated coronal jets to the eruption of socalled mini-filaments, whose plasma provides most of the ejected material (Shen et al, 2012;Adams et al, 2014;Sterling et al, 2015Sterling et al, , 2016Panesar et al, 2016;Joshi et al, 2018;Yang and Zhang, 2018;Moore et al, 2018). Even in cases of lower resolution observations, mini-filament reformation and eruption has been postulated as the origin of a series of blow-out jets and related events (Chandra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%